Proses Awal dalam Penghasilan Komposisi “Kelampan Bajang” dengan Mengadaptasi Struktur Musik Pop Suku Sasak Lombok - Sapriadi Sapriadi; Chamil Arkhasa Nikko Mazlan; Affendi Ramli (Musikolastika: Jurnal Pertunjukan dan Pendidikan Musik, 2021)
The musical composition, entitled Kelampan Bajang, is the main narrative of the composition theme about the story of the journey of the young Sasak tribe which is semiotically depicted in three different times, namely morning, afternoon, and night. This composition emerged due to several phenomena found, including 1) there are no complete Sasak songs in transcripts and arrangements, 2) many musicians arrange songs in Sasak but often cause controversy in lyrics and music, 3) many talented young musicians cover repeating noname songs on several songs performed by many pop singers in Lombok, 4) many sasak pop songs but most of them do not represent local culture in terms of lyrics and music. This paper aims to explain the initial process of musical composition with the theme Kelampan Bajang including 1) Bekuliq, 2) Bekayaq, 3) Matur Tampiasih, 4) Sepi Alam Dese, 5) Lalo Midang, and 6) Merariq. All song lyrics are written in the Sasak language. The research uses the autoethnographic method to discuss the problem, how the idea of ​​creating musical compositions can be aligned with the diversity of musical culture in Lombok. After conducting an in-depth study, the author concluded that in order to create a compositional work that could represent regional culture and not cause controversy among the public, namely 1) the author inserted an exploration of the pelog and slendro melodic motifs in the vocal melody section as regional identity, 2) the author inserted the motif the melodies of pelog and slendro in the musical arrangement section, and 3) the author uses good and correct local language lyrics that are in accordance with the regional culture in Lombok.